PENERAPAN ANALISIS KORELASI SPEARMAN’S RANK PADA WAITING LIST JAMAAH HAJI DI INDONESIA - Kurniawan, Muh Idham (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2023)
The imbalance between the number of registrants and the quota for Hajj pilgrims in Indonesia means that the Indonesian people have to be patient when departing for the holy land with a waiting list period of at least 48 years. The large number of registrants for Hajj pilgrims and the length of the waiting list for prospective Hajj pilgrims make researchers interested in testing whether there is a relationship between the number of registrants and the length of the waiting list for Hajj pilgrims in Indonesia. In this study, researchers used Spearman correlation analysis. The results of this research are that the correlation between the number of registrants and the waiting time for Hajj pilgrims in Indonesia is 50.6% with a sig (0.000) < α_(5%) so it can be concluded that there is a relationship between the number of registrants and the waiting time for Hajj pilgrims in Indonesia.